2007
DOI: 10.1089/ast.2006.0112
|View full text |Cite
|
Sign up to set email alerts
|

Adenine Synthesis in Interstellar Space: Mechanisms of Prebiotic Pyrimidine-Ring Formation of Monocyclic HCN-Pentamers

Abstract: The question whether the nucleobases can be synthesized in interstellar space is of fundamental significance in considerations of the origin of life. Adenine is formally the HCN pentamer, and experiments have demonstrated that adenine is formed under certain conditions by HCN pentamerization in gas, liquid, and condensed phases. Most mechanistic proposals invoke the intermediacy of the HCN tetramer AICN (4), and it is thought that adenine synthesis is completed by addition of the 5(th) HCN to 4 to form amidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 49 publications
4
52
0
Order By: Relevance
“…During the review of this article, Glaser et al (32) proposed and analyzed mechanisms of pyrimidine-ring formation of isomeric monocyclic HCN pentamers. Pyrimidine-ring formation from a monocyclic HCN pentamer, either by proton-catalyzed or by uncatalyzed cyclization, was found not to be viable thermochemically.…”
Section: Methodsmentioning
confidence: 99%
“…During the review of this article, Glaser et al (32) proposed and analyzed mechanisms of pyrimidine-ring formation of isomeric monocyclic HCN pentamers. Pyrimidine-ring formation from a monocyclic HCN pentamer, either by proton-catalyzed or by uncatalyzed cyclization, was found not to be viable thermochemically.…”
Section: Methodsmentioning
confidence: 99%
“…One can also envision the formation of 8h by direct NH 3 elimination from 63 (consider resonance form 63-B) via 68 or from 65 via 67 if 65 does not reclose to 16= [51]. These options depend on the accessibilities of 63 and 65.…”
Section: Esi-ms/ms Of Adenosinementioning
confidence: 99%
“…Glaser (2007) reported that the DFT calculations are widely used in the chemistry community because it succeeds in reproducing the experimental data with high reliability. The geometries of the reactants, products, intermediates, and transition states were calculated using the DFT with the B3LYP functional with a 6 − 311G+(2df, 2p) basis set, and we improved the energy description even more by single-point calculations with hybrid meta exchange correlation DFT functionals M06 and M06 − 2X to calibrate the high computational cost and low-level calculations.…”
Section: Methodsmentioning
confidence: 99%